Contextualism vs. Mubādalah: Comparative Islamic Legal Methodologies for Gender Equality - Abdul Basith; Kerwanto Kerwanto (Jurnal Syariah dan Hukum Komparatif, 2026)
Gender equality has become a central concern in contemporary Islamic legal interpretation, prompting the development of new hermeneutical approaches. This study compares Nasaruddin Umar’s contextualist methodology and Faqihuddin Abdul Kodir’s mubādalah framework to assess their contributions to gender-just Qur’anic interpretation. The research employs a qualitative descriptive design with a comparative library-based approach. Primary data are drawn from the major works of both scholars and applied to two contested gender-related verses, Q.S. al-Nisā’ [4]:34 and Q.S. al-Baqarah [2]:228. The analysis shows that Nasaruddin Umar emphasizes historical contextualization and feminist hermeneutics to deconstruct patriarchal readings, while Faqihuddin Abdul Kodir applies a reciprocity-based, maqāṣid-oriented approach that reconstructs gender relations as egalitarian partnerships. Both methodologies reject hierarchical interpretations and reinterpret authority and responsibility as functional and ethical rather than ontological. Despite methodological differences, the two approaches converge in promoting justice, mutuality, and human dignity as core principles of Islamic legal reasoning. Their complementary perspectives demonstrate that methodological plurality can strengthen efforts to advance gender equality within contemporary Islamic jurisprudence.